2010
DOI: 10.1017/s1751731110001321
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different types of stressors during mid- and late pregnancy on lamb weight and body size at birth

Abstract: Mid-pregnancy shearing has consistently been shown to increase lamb birth weight, which can lead to an increase in lamb survival rates. However, shearing ewes during the winter months and under outdoor pastoral farming conditions can expose the recently shorn ewe to a greater risk of hypothermia. The aim of this study was to determine if exposure of ewes to repeated stressors, in mid-and late pregnancy, would result in an increase in lamb birth weight. This information may assist in the elucidation of the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The ewe must first have the potential to respond (lambs born to unshorn ewes destined to have low birth-weight) and secondly, the ability to respond to shearing (adequate maternal body reserves or nutrition). The absence of an increase in birth-weight in response to maternal shearing observed in singleton lambs by Corner et al (2007Corner et al ( , 2010b and Jenkinson et al (2009) could be ascribed to the first of the above criteria. However, Kenyon et al (2004) failed to find any interaction between ewe body condition score (BCS) (over a wide range) and response to shearing.…”
Section: Shearingmentioning
confidence: 91%
See 1 more Smart Citation
“…The ewe must first have the potential to respond (lambs born to unshorn ewes destined to have low birth-weight) and secondly, the ability to respond to shearing (adequate maternal body reserves or nutrition). The absence of an increase in birth-weight in response to maternal shearing observed in singleton lambs by Corner et al (2007Corner et al ( , 2010b and Jenkinson et al (2009) could be ascribed to the first of the above criteria. However, Kenyon et al (2004) failed to find any interaction between ewe body condition score (BCS) (over a wide range) and response to shearing.…”
Section: Shearingmentioning
confidence: 91%
“…Other responses Corner et al (2006bCorner et al ( , 2007Corner et al ( , 2010b focussed on the effects of shearing ewes in mid-pregnancy in conjunction with other treatments. In the first experiment (Corner et al 2006b), ewes were gathered on GD80, fasted for 24 h and then shorn or not shorn.…”
Section: Shearingmentioning
confidence: 99%
“…Any metabolic stress therefore affects wool production [4], particularly if the diversion of body reserves to the fetus and new-born lambs leads to deficiencies in trace elements or sulphur amino acids [5,6]. The relationship between pregnancy and wool production is illustrated by the enhancement of fetal growth and birth weight when ewes are shorn in mid- or late pregnancy [7,8]. Brown et al [9] and Rose [10] have suggested that the competition for nutrients is greater during pregnancy than lactation, although litter size was not assessed in either of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to stipulate pregnancy as the only variable affecting wool cortisol concentrations. Other environmental factors include access to water, nutrition, climate and predation have also been shown to affect long-term cortisol concentrations [10, 17, 22] and cannot be excluded as potential extrinsic influences within the present study.…”
Section: Discussionmentioning
confidence: 99%